Android-Based Interactive Media to Raise Student Learning Outcomes in Social Science - Sujarwo; Herawati, Septy Nur; Sekaringtyas, Tunjungsari; Safitri, Desy; Lestari, Ika; Suntari, Yustia; Umasih; Marini, Arita; Iskandar, Rossi; Sudrajat, Ajat (International Journal of Interactive Mobile Technologies (iJIM), 2022)
Learning media is one of the important components in the process of implementing learning, especially during the current pandemic. But in reality there are still few teachers who use media in the learning process, causing student learning outcomes to decline. Interactive media which is one of the media that can be used to attract students' attention by combining systems ranging from text, images, videos, and audio/sound can provide new experiences for students in learning. This study aims to determine student learning outcomes after using android-based interactive learning media in social science subjects. The population group consisted of 70 students from several schools in Cluster 2, Cipinang Muara Village. Then samples were taken using the Slovin formula to get 60 samples of fourth grade students. This study uses experimental research methods and uses a single group pre test - post test. The collected data were analyzed through t test. The results showed that android-based interactive media had a positive effect on student learning outcomes. Students experienced a significant increase in learning outcomes by using this media. In addition, students feel more interested and easier to understand the material by using this application. The results showed that android-based interactive media had a positive effect on student learning outcomes. Students experienced a significant increase in learning outcomes by using this media. In addition, students feel more interested and easier to understand the material by using this application. The results showed that android-based interactive media had a positive effect on student learning outcomes. Students experienced a significant increase in learning outcomes by using this media. In addition, students feel more interested and easier to understand the material by using this application.